Differences in the clinical characteristics of papillary thyroid microcarcinoma located in the isthmus ≤5 mm and >5mm in diameter - Zhu, Feng; Zhu, Lixian; Shen, Yibin; Li, Fuqiang; Xie, Xiaojun; Wu, Yijun (Frontiers in Oncology, 2022)
Background: The optimal treatment of papillary thyroid microcarcinomas (PTMC) located in the isthmus (iPTMCs) is still controversial. The purpose of this study was to compare the clinicopathologic features of patients with iPTMCs ≤5 mm and >5 mm in diameter after total thyroidectomy and to identify risk factors for recurrence in patients with iPTMCs. Methods: 102 iPTMC patients who underwent total thyroidectomy were reviewed retrospectively. The clinicopathologic characteristics of iPTMCs ≤5 mm group (n=29) has been compared to a group >5 mm (n=73). Univariate and multivariate Cox proportional hazard models served to identify risk factors associated with recurrence-free survival (RFS). Results: Gender (p=0.033), multifocality (p=0.041) and central lymph node metastasis (CLNM) (p=0.009) of patients in the ≤5 mm and >5 mm groups differed significantly. iPTMC patients with Age <55 years, male, multiple tumor and extrathyroidal extension showed comparatively more frequent of CLNM in >5 mm groups. Of the 102 patients, 9 (8.8%) developed recurrence during follow-up (median 49.5 months). The patients with recurrences had comparatively high rates of CLNM (p=0.038), extranodal invasion (p=0.018), and more MNCND (Metastasis Nodes for Central Neck dissection) (p=0.020). A cut-off of MNCND >2.46 was established as the most sensitive and specific level for the prediction of recurrence based on receiver operating characteristic (ROC) curve analyses. Multivariate analysis showed that the number of MNCND ≥3 was an independent predictor of poor RFS (p = 0.028). Conclusion: We have found that the recurrence rates are similar in patients with iPTMCs ≤5 mm and >5 mm. The iPTMCs >5 mm was more likely to be associated with pathological features such as multifocality and CLNM. The male gender, extrathyroidal extension and CLNM were associate with recurrence of iPTMCs except for tumor size and multifocality. Higher risk of CLNM should be considered in iPTMC >5 mm when reaches some risk factors. The numbers of MNCND ≥3 may be an independent predictor for recurrence, which could help clinicians for the decision of radioiodine administration and the modulation of follow-up modalities.